Strategi Guru Pendidikan Agama Islam Dalam Peningkatan Kedisiplinan Siswa (Penelitian Studi Kasus Di Sekolah Dasar Negri 1 Pasirkupa Lebak-Banten) - Mahpudin, Pupu; Alfarisi, Aris Salman (LPPM STAI La Tansa Mashiro, 2024)
Islamic education is education that aims to guide children to have Muslim personalities, namely individuals who submit and obey the rules of Islam, as well as guide their way of life. The Islamic Religious Education curriculum states that Islamic Religious Education is a conscious and planned effort to prepare students to know, understand, appreciate and believe in the teachings of the Islamic religion, be devout and have noble character in practicing the Islamic religion from its main sources, the holy books of the Koran and Hadith. The aims of this research are 1) To find out what strategies are used by teachers in the process of improving discipline at SDN 1 Pasirkupa, 2) To find out how to improve student discipline at SDN 1 Pasirkupa. This research uses a qualitative type with case study research methods, the data source is Islamic Education Teachers, data collection techniques use observation, interviews and documentation, data analysis is by data reduction, data presentation and drawing conclusions.The results of the research show that 1) The strategies carried out by teachers in the Islamic Religious Education process at SDN 1 Pasirkupa, namely: a) providing lesson content to students, b) Presenting the information/materials needed for learning, c) Fulfilling the system learning approach. 2) Disciplinary violations committed by students at Sobang 1 State Vocational School, namely:a) Discipline in terms of time, b) Discipline in terms of attitude and personality, c) Discipline in terms of appearance and neatness. Keywords: Islamic Religious Education (PAI) Teacher, Student Discipline